Application of Fuzzy Logic to Find Out the Amount of Spending Money at the Bank - Doms Upuy; Feronika Leunupun; Yopi A Lesnussa; Zeth A Leleury; Arlene H. Hiariey (PT FORMOSA CENDEKIA GLOBAL, 2022)
Banking is an important part of the financial system for smoothly running a country's economic activities. Quality of service is a form of consumer assessment of the level of service, and the factors that influence service quality include factors of employees, systems, technology, and customer involvement. Banking services are carried out to make it easier for customers to make transactions. The needs faced by customers cause the spending of money at the bank to be often not properly controlled. For example, for money withdrawn in large or small amounts for daily needs, fuzzy logic is used to make it easier for customers to know the amount of money spent each month. Given these problems, the authors are motivated to do further research in solving the case with the fuzzy method. Based on the data obtained from the bank, by utilizing fuzzification, fuzzy inference, and fuzzy rule base, as well as defuzzification of fuzzy logic, fuzzy logic can be applied to determine the amount of money spent. The research results show nine sales functions (Membership Function) from two input parameters, namely withdrawal of money and remaining balance. The linguistic variables used are Little Expenditure, Moderate Expenditure, Much Expenditure, Little Balance, Moderate Balance, and Many Balance.